Architectural archetype and changes in the visual identity of the Pinacoteca since the 1990s - Piaia, Jade Samara (Arcos Design, 2023)
This article’s aim is to record part of an investigation about Pinacoteca de São Paulo graphic memory. The objective was to understand how the process of the image’s visual association of the museum’s building with its graphic signature in the 1990s occurred. The methods were to survey and analyze this graphic memory, using interviews with designers who worked for the institution in this period. The conclusions point to a conjuncture of political, historical and structural factors that influenced the incorporation of the building into the visual identity of the institution.